Trends in the Incidence of Bronchopulmonary Dysplasia after the Introduction of Neurally Adjusted Ventilatory Assist (NAVA) - Kashish Mehra; Mitchell Kresch (MDPI AG, 2024)
Objective: This study investigates the difference in the rates of bronchopulmonary dysplasia in very low birth weight infants before and after the introduction of neurally adjusted ventilatory assist (NAVA). Study Design: A retrospective cohort study comparing rates of Bronchopulmonary dysplasia (BPD) before and after implementation of NAVA. Eligibility criteria included all very low birth weight VLBW neonates needing ventilation. For analysis, each cohort was divided into three subgroups based on gestational age. Changes in the rate of BPD, length of stay, tracheostomy rates, invasive ventilator days, and home oxygen therapy were compared. Results: There were no differences in the incidence of BPD in neonates at 23-25 6/7 weeks' and 29-32 weeks' gestation between the two cohorts. A higher incidence of BPD was seen in the 26-28 5/7 weeks' gestation NAVA subgroup compared to controls (86% vs. 68%, p = 0.05). No significant difference was found for ventilator days, but infants in the 26-28 6/7 subgroup in the NAVA cohort had a longer length of stay (98 ± 34 days vs. 82 ± 24 days, p = 0.02), a higher percentage discharged on home oxygen therapy (45% vs. 18%, respectively, p = 0.006), and higher tracheostomy rates (3/36 vs. 0/60, p = 0.02), compared to the control group. Conclusions: The NAVA mode was not associated with a reduction in BPD when compared to other modes of ventilation. Unexpected increases were seen in BPD rates, home oxygen therapy rates, tracheostomy rates, and the length of stay in the NAVA subgroup born at 26-28 6/7 weeks' gestation.